Perspectives and Difficulties of Green Marketing: An analysis in the context of Bangladesh (International Journal of Scientific Research and Management (IJSRM), 2024)
Green marketing is a method of using the environmental advantages of a product or service to boost sales. Many buyers would prefer goods that do not affect the environment rather than less eco-friendly products, even though they cost more. Marketers rely on the sustainability advantages of advertising items such as recyclable diapers, energy-efficient light bulbs, and eco-friendly detergents for green marketing. Business and the climate are also interrelated issues in today’s business world. Marketing plays an essential role in solving this environmental business world problem. Nearly every government in the world worries about ecological or renewable goods and marketing issues. The paper discusses the opportunities and obstacles of green marketing in Bangladesh. The article also explains why businesses embrace it and concludes that green marketing will continue expanding in nature and demand.